Phenomenological vs. biophysical models of thermal stress in aquatic eggs. (28th November 2016) - Martin, Benjamin T.; Pike, Andrew; John, Sara N.; Hamda, Natnael; Roberts, Jason; Lindley, Steven T.; Danner, Eric M.
Abstract: Predicting species responses to climate change is a central challenge in ecology. These predictions are often based on lab‐derived phenomenological relationships between temperature and fitness metrics. We tested one of these relationships using the embryonic stage of a Chinook salmon population. We parameterised the model with laboratory data, applied it to predict survival in the field, and found that it significantly underestimated field‐derived estimates of thermal mortality. We used a biophysical model based on mass transfer theory to show that the discrepancy was due to the differences in water flow velocities between the lab and the field. This mechanistic approach provides testable predictions for how the thermal tolerance of embryos depends on egg size and flow velocity of the surrounding water. We found support for these predictions across more than 180 fish species, suggesting that flow and temperature mediated oxygen limitation is a general mechanism underlying the thermal tolerance of embryos.